Clinical Correlation with Coronary Circulation - Bakar, Sheikh Muhammad Abu; Sultan, Md Ashraf Uddin; Salman, Mohammad; Siddique, Md Abu; Ahmed, Md Khurshed; Sarkar, Jogendra Nath; Fatema, Nilufar (University Heart Journal, 2011)
DOI: 10.3329/uhj.v6i2.7252 University Heart Journal Vol. 6, No. 2, July 2010 pp.86-89